2017
DOI: 10.1039/c7cc00467b
|View full text |Cite
|
Sign up to set email alerts
|

Distinct activation of Cu-MOR for direct oxidation of methane to methanol

Abstract: NO activation of Cu-MOR enhanced methanol production at elevated temperatures, to a greater extent than activation by O under optimal conditions. The increase in methanol production by NO activation was attributed to the facile formation of an active copper center with no formation of inactive intermediate species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
80
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 20 publications
7
80
1
Order By: Relevance
“…Higher O 2 activation temperature has been shown to increase the yield for Cu‐CHA and Cu‐MOR ,. Analogous observations were made here: an increment in productivity of 56 μmol/g is observed when moving from 400 to 500 °C (Figure a).…”
Section: Resultssupporting
confidence: 84%
“…Higher O 2 activation temperature has been shown to increase the yield for Cu‐CHA and Cu‐MOR ,. Analogous observations were made here: an increment in productivity of 56 μmol/g is observed when moving from 400 to 500 °C (Figure a).…”
Section: Resultssupporting
confidence: 84%
“…Also in this study, a [Cu 3 (μ‐O) 3 ] 2+ core was suggested to be responsible for the activation of methane. A similar result was reported recently by Kim et al . In addition, several other Cu sites embedded in the zeolite channels have been proposed as potential sites for the activation of methane, namely, a simple monocopper site, larger Cu oxo clusters such as [Cu 4 O 4 ] 2+ and [Cu 5 O 5 ] 2+ , and even small/ultrasmall CuO clusters ,…”
Section: Resultsmentioning
confidence: 99%
“…After interaction with methane at 473 Ka nd 7bar and subsequent introduction of aw ater-containing helium flow,d esorption of methanol began after ac ertain induction period, which is associated with gradual saturation of the samples with water. [11] Quantitative assessment of the amount of methanol formed over different samples (Table 1) points to ag radual increase in the methanol yield per mole of copper with an increase in the Si/Al ratio;atthe same time,the selectivity of methane conversion differed over these samples.T oa ddress this point, we applied in situ infrared spectroscopy,w hich allowed us to observe the surface species.T he spectra obtained after the interaction of methane at 473 Kw ith oxygen-activated samples followed by evacuation are given in Figures 2a and S4. Fors amples with Si/Al ratios of 6.5 or 10, the slow desorption of methanol is related to the higher amount of aluminum and residual Brønsted sites,w hich can interact with methanol molecules owing to their high affinity to polar molecules.N o hydrogen formation was observed after the introduction of water on O 2 -activated samples ( Figure 1, insets), which is in line with our previous study.…”
mentioning
confidence: 99%
“…[1][2][3][4] Another open question deals with the role of the nature of the oxidant, as well as the mechanism of methane oxidation and regeneration of the copper oxide active site. [9][10][11][12] We recently proposed an alternative solution to the above problem by showing that selective anaerobic oxidation of methane is possible; [13] water can be used both to provide oxygen to regenerate the zeolite active sites and to stabilize reaction intermediates,w hich uniquely occurs in the copper zeolite,t od rive the otherwise endothermic Cu I oxidation reaction. [9][10][11][12] We recently proposed an alternative solution to the above problem by showing that selective anaerobic oxidation of methane is possible; [13] water can be used both to provide oxygen to regenerate the zeolite active sites and to stabilize reaction intermediates,w hich uniquely occurs in the copper zeolite,t od rive the otherwise endothermic Cu I oxidation reaction.…”
mentioning
confidence: 99%